Psychoneuroimmunology Aspects of COVID-19 Pandemic - Yuliana, Yuliana (Medica Hospitalia : Journal of Clinical Medicine, 2020)
BACKGROUND: In December 2019 the world was struck by an outbreak of a disease in China which is now referred to as Coronavirus disease (COVID-19). COVID-19 disease is a viral infection caused by SARS-CoV-2. This disease has spread very quickly throughout the world, causing significant social and economic impacts. Now this incident is called a pandemic. There are many controversial theories up till now, especially about psychoneuroimmunology aspects. Symptoms caused by this disease vary greatly from the main attack of the respiratory system to neuro immunity system. Immune response is the key factor to invasion of this virus into the human body. OBJECTIVE: The aim of this paper is providing comprehensive understanding regarding psychoneuroimmunology aspects of COVID-19 infection in those variable symptoms. DISCUSSION: Neurological symptoms might start from anosmia, loss of taste (ageusia), delirium, encephalitis, Guillain-Barre syndrome, and stroke. Behavior might be affected with specific symptom such as depression and psychosis. Neuropsychiatric sequelae had been found in past viral pandemics. CONCLUSION: Psychoneuroimmunology aspects will determine the variability of symptoms of each patient. Comprehensive understanding of psychoneuroimmunology perspective will aid in promoting post-pandemic public mental health in order to handle COVID-19 properly and minimize socio-economic impacts.